New phenomenological model for comparison of lasers with different temporal outputs - Coroado, Julio; Williams, Stewart W.; Suder, Wojciech; Ganguly, Supriyo; Meco, Sonia; Pardal, Goncalo (Springer, 2022)
Laser welding is distinguished by low heat input, low distortion, high travel speeds and accuracy. Traditional high-power pulsed wave (PW) lasers are being replaced by high-frequency low-pulse energy fibre lasers. However, as these lasers operate at very high frequencies, near continuous wave (CW) operation, it is not clear the benefit of such frequencies in comparison to CW lasers for micro-welding. In this project, two lasers, one in high-frequency PW and another in CW are operated at the same conditions, including average power, average peak power, spot size and travel speed, and the differences in material response are investigated. It has been shown that frequency is one of the important parameters that affect the heat loss between individual pulses, referred to as inter-pulse losses. At low frequency, the PW laser provided lower melting efficiency and higher penetration efficiency than CW. On the other hand, at high frequency, the PW resulted in lower melting and penetration efficiency than CW. In addition, a new definition of interaction time has been proposed to capture conduction losses by travel speed and heat inter-pulse losses due to periodic lack of laser power. This allows a like-for-like comparison of CW and PW lasers and can be used to predict penetration depth with processing parameters.
Keywords: Laser welding; CW and PW modes; Inter-pulse spacing; Weld shape; Stainless steel